Detection of Flavonols from Tragia plukenetii A.R.Smith - Kankute, V.T.Narwade, A.A.Waghmare; S.R. (Recent Research in Science and Technology, 2011)
Flavonols from Tragia plukenetii A.R. Smith were extracted by using different solvent and they were identified and detected by Paper Chromatography (PC) and spectroscopic method. Flavonols like kaempferol, Quercetin were detected from T.plukenetii A.R.Smith.